Extracellular vesicles as reconfigurable therapeutics for eye diseases: Promises and hurdles. (June 2023) - Shekari, Faezeh; Abyadeh, Morteza; Meyfour, Anna; Mirzaei, Mehdi; Chitranshi, Nitin; Gupta, Vivek; Graham, Stuart L.; Salekdeh, Ghasem Hosseini
Abstract: A large number of people worldwide suffer from visual impairment. However, most available therapies rely on impeding the development of a particular eye disorder. Therefore, there is an increasing demand for effective alternative treatments, specifically regenerative therapies. Extracellular vesicles, including exosomes, ectosomes, or microvesicles, are released by cells and play a potential role in regeneration. Following an introduction to EV biogenesis and isolation methods, this integrative review provides an overview of our current knowledge about EVs as a communication paradigm in the eye. Then, we focused on the therapeutic applications of EVs derived from conditioned medium, biological fluid, or tissue and highlighted some recent developments in strategies to boost the innate therapeutic potential of EVs by loading various kinds of drugs or being engineered at the level of producing cells or EVs. Challenges faced in the development of safe and effective translation of EV-based therapy into clinical settings for eye diseases are also discussed to pave the road toward reaching feasible regenerative therapies required for eye-related complications.